2008
DOI: 10.1007/s00784-008-0220-x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of denture cleansers on denture liners contaminated with Candida species

Abstract: As poor denture hygiene is related to Candida colonisation, disinfectant solutions have been proposed as an effective method of preventing denture stomatitis. This study assessed the efficacy of denture cleansers on Candida albicans and Candida glabrata adherence on denture liners. Another aim was to correlate materials' surface roughness (Ra) to Candida adherence. Specimens of three denture liners (soft and hard polymethyl methacrylate (PMMA)-based and soft silicone-based) were prepared and had their Ra measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
78
0
19

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(106 citation statements)
references
References 28 publications
9
78
0
19
Order By: Relevance
“…As alternative cleaning methods, chemical cleaning such as soaking in sodium hypochlorite 8) or denture cleansers 9) are known to be effective. Sodium hypochlorite is commonly used as a disinfectant as it is highly bactericidal and fungicidal 10) ; however, it decolorizes the denture materials and corrodes the metals 9) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As alternative cleaning methods, chemical cleaning such as soaking in sodium hypochlorite 8) or denture cleansers 9) are known to be effective. Sodium hypochlorite is commonly used as a disinfectant as it is highly bactericidal and fungicidal 10) ; however, it decolorizes the denture materials and corrodes the metals 9) .…”
Section: Introductionmentioning
confidence: 99%
“…Sodium hypochlorite is commonly used as a disinfectant as it is highly bactericidal and fungicidal 10) ; however, it decolorizes the denture materials and corrodes the metals 9) . Immersion in denture cleanser is more effective than washing the TC with water 11) .…”
Section: Introductionmentioning
confidence: 99%
“…The literature has shown that sodium hypochlorite and alkaline peroxides are the two main classes of immersion denture cleansers 27 . Sodium hypochlorite is inexpensive, presents bactericidal and fungicidal action, as well as stain removal properties, requires a short period of disinfection, and have been suggested as effective denture cleansers [28][29][30] . Moreover, alkaline hypochlorite cleansers contain 5% sodium hypochlorite act directly on organic matrix of plaque causing dissolution of polymer structure.…”
Section: Discussionmentioning
confidence: 99%
“…However, NaOCl was used in a low concentration (0.5%), which seems to present no detrimental effect on resilient denture liners. 15,16 This result is important since this concentration may result in adequate control of biofilm formation without alteration the original characteristics of the denture liners. However, it is worth saying that in this study, the effects on the assessed properties of resilient liners were tested only for 14 days and this may have influenced the results, especially considering that other liners may be used for longer periods.…”
Section: Discussionmentioning
confidence: 99%